MEMBANGUN PARTISIPASI MASYARAKAT DI ERA OTONOMI DAERAH (STUDI KRITIS PARTISIPASI ULAMA DALAM PENYUSUNAN PERATURAN DAERAH DI KABUPATEN BANYUMAS) - Nita Triana (IAIN Purwokerto, 2020)
This study was aimed at explaining comprehensively the social participation, especially from religious leader or Ulama in composing District Rules (Perda) on Traditions. This is a nondoctrinal study with a qualitative method. Data were collected through interviews, observations, and document studies with sociolegal approach. Data were analyzed using interactive cycles of Strauss and J Corbin. The result showed that: the participation of religious leaders (Ulama) in composing Perda was at the level of tokenism, meaning that it seemed they had a participation in the activity, but it was not a real participation. They were invited to at the dicussion on development planning and socialization of the Perda. The problem related to the application of this system of participation was that the government bureaucracy was still not transparent and participative. Culturally, there was a patron-client tradition, i.e. the government was the patron or designer that determined the pattern, while the society realized what had been patronized by the government. It is necessary to build a responsive and participative law of bureaucracy both from the government and ulama. It can be realized if there is a continuous communication between the government and ulama.